Transposon-induced epigenetic silencing in the X chromosome as a novel form of dmrt1 expression regulation during sex determination in the fighting fish - Wang, Le (2022)
Background: Fishes are the one of the most diverse groups of animals with respect to their modes of sex determination, providing unique models for uncovering the evolutionary and molecular mechanisms underlying sex determination and reversal. Here, we have investigated how sex is determined in a species of both commercial and ecological importance, the Siamese fighting fish Betta splendens. Results: We conducted association mapping on four commercial and two wild populations of B. splendens. In three of the four commercial populations, the master sex determining (MSD) locus was found to be located in a region of ~ 80 kb on LG2 which harbours five protein coding genes, including dmrt1, a gene involved in male sex determination in different animal taxa. In these fish, dmrt1 shows a male-biased gonadal expression from undifferentiated stages to adult organs and the knockout of this gene resulted in ovarian development in XY genotypes. Genome sequencing of XX and YY genotypes identified a transposon, drbx1, inserted into the fourth intron of the X-linked dmrt1 allele. Methylation assays revealed that epigenetic changes induced by drbx1 spread out to the promoter region of dmrt1. In addition, drbx1 being inserted between two closely linked cis-regulatory elements reduced their enhancer activities. Thus, epigenetic changes, induced by drbx1, contribute to the reduced expression of the X-linked dmrt1 allele, leading to female development. This represents a previously undescribed solution in animals relying on dmrt1 function for sex determination. Differentiation between the X and Y chromosomes is limited to a small region of ~ 200 kb surrounding the MSD gene. Recombination suppression spread slightly out of the SD locus. However, this mechanism was not found in the fourth commercial stock we studied, or in the two wild populations analysed, suggesting that it originated recently during domestication. Conclusions: Taken together, our data provide novel insights into the role of epigenetic regulation of dmrt1 in sex determination and turnover of SD systems and suggest that fighting fish are a suitable model to study the initial stages of sex chromosome evolution.